2020
DOI: 10.1111/odi.13419
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of extracellular matrix‐remodeling factors in lymph nodes from oral cancer patients

Abstract: Objective Most malignant tumors require remodeling extracellular matrices (ECMs) for invasive growth and metastasis. Cancer cells and stromal cells remodel ECM. We investigated the relationship between regional lymph node (LN) metastasis and expression of ECM‐remodeling factors in oral squamous cell carcinoma (OSCC). Methods Using primary OSCC and cervical LNs obtained surgically, we performed immunohistochemical evaluation of the ECM‐remodeling factors, lysyl oxidase (LOX), MT1‐MMP, S100A8, and TIMP‐1 in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Increased fibrinogen deposition was found in tumor-draining LNs compared to control LNs [92]. Furthermore, enhanced production of ECMremodeling factors such as LOX, MT1-MMP and TIMP-1 was detected in metastatic LNs from patients with oral cancer [166]. This was in line with the implication of LOX and MMPs in the liver and lung pre-metastatic niches [167][168][169][170].…”
Section: Ln Extracellular Matrix Remodeling In the Pre-metastatic Nichesupporting
confidence: 65%
“…Increased fibrinogen deposition was found in tumor-draining LNs compared to control LNs [92]. Furthermore, enhanced production of ECMremodeling factors such as LOX, MT1-MMP and TIMP-1 was detected in metastatic LNs from patients with oral cancer [166]. This was in line with the implication of LOX and MMPs in the liver and lung pre-metastatic niches [167][168][169][170].…”
Section: Ln Extracellular Matrix Remodeling In the Pre-metastatic Nichesupporting
confidence: 65%
“…MMP14 localises at the surface-membrane expression in OSCC, particularly in the invasive area, and promotes extracellular matrix degradation [28, [29][30][31]. In addition, MMP14 derived from tumour cells activates mesenchymal cells and CAFs in the TME [32][33][34][35][36]. CAFsderived MMP14 releases the matrix, promoting OSCC invasion [28][29][30][31]37].…”
Section: Discussionmentioning
confidence: 99%
“…MMP2, 3, 9, and 14, derived from CAFs and tumour cells in OSCC, are important enzymes for metastasis [38][39][40][41][42]; however, their role in ENE development has not been examined. In vivo studies have revealed that MMP14 in the TME creates a suitable primary and pre-metastatic niche in the LN for tumour survival during epithelial-mesenchymal transition (EMT) [32][33][34][35][36]. This may be a reason for the similar expression pro les of MMP14 at the TSI and ENE sites.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of connexin-43 and E-cadherin was also found in the metastatic lymph nodes of gastric cancer [ 153 ]. Furthermore, an increase in enzymes such as lysyl oxidase, membrane type-matrix metalloproteinase and tissue inhibitor of matrix metalloproteinase 1 were associated with ECM degradation in the metastatic lymph nodes of patients with oral cancer [ 154 ]. In contrast, high levels of fibronectin, tenascin-C, and osteopontin in tumor stroma have been shown to be associated with lymph node metastasis [ 155 , 156 ].…”
Section: Metastatic Spread Via Blood and Lymphatic Vesselsmentioning
confidence: 99%